Coal Mining Sub-Sectors in Taxation: An Overview of Characteristic Factors - Permana, Cahya Bagus; Oktafiyani, Melati (Jurnal Penelitian Ekonomi dan Bisnis, 2022)
Tax Avoidance is a legal effort made by companies to minimize the payment of their business tax obligations to the tax authorities by taking advantage of existing tax regulation loopholes or those that have not been regulated in statutory regulations. Even if this action is legal, the government does not want it because it is unable to optimize tax revenues. Moreover, the company will benefit from tax avoidance whenever possible. This study aims to determine whether firms’ characteristics variables influence tax avoidance. This study covers a population of 25 coal mining companies listed on the Indonesia Stock Exchange from 2014 to 2019. Using a purposive sampling technique, eight coal mining companies were selected as part of this study. The study uses SPSS data processing tools, and the data is analysed by multiple linear regression analysis. The findings showed that the firm characteristics represented by the variables of size, leverage, age, and sales growth did not affect tax avoidance, while the profitability variable affected tax avoidance. The results indicate that the variability of firm characteristics may explain the Tax Avoidance of 18.9%, while the remaining 81.1% can be explained by other variables. Keywords:sizeprofitabilityleveragesales growthtax avoidance